Prevalence of Cardiovascular Drugs Among Pregnant Women in Sudan - Haj Elamin. E. Azhari, Siddiqa M. A. Hamza, Mohammed. R.R, H. E. Omer, A. M. Iman, Entesar Mohammed Abdulla Tabein, Hadeil M. E. Idris (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Pregnant women with heart disease present multiple medical dilemmas. Pregnancy-related physiological changes impair the heart’s ability to respond to pathological processes such as hypertension and heart failure. Aim: The current study’s aim is to elicit data on cardiovascular medication use during pregnancy. Methods: This is a descriptive, retrospective, cross-sectional, hospital-based study, carried out in Military Hospitals and Khartoum Teaching Hospital, in Sudan. A data collection form was utilized to gather information from 650 patient files of pregnant women. Results: 650 subjects met the study criteria; 7% of women (N=46) were dispensed cardiovascular medications, the consumption being significantly higher in the third trimester (7-9 months) in 78.26% (p<0.05). The most common cardiovascular drugs dispensed were Methyldopa (N=26, 4.0%), Heparin (N=9, 1.3%), Nifedipine (N=7, 1.0%), Hydralazine (N=2, 0.3%) and Diazepam (N=2, 0.3%). Methyldopa is the commonest in the all trimesters - first (1-3 months) (N=2, 0.3%), second (4-6 months) (N=4, 0.6%) and third (7-9 months) (N=20, 3.0%). Nifedipine and Diazepam were used only in the third trimester. Conclusions: There are many clinical situations requiring cardiovascular medications in pregnancy. Thus, it is necessary to conduct frequent health educational programs educating pregnant women about the risk factors for pregnancy-induced cardiovascular disease, and proper use of medication.